Exploring the Dynamics of Employee Loyalty in Construction Companies - Tarihoran , Tumpak; Harsono, Regina Deti Mulyo (Jurnal E-Bis, 2025)
In the challenging construction industry, employee loyalty is crucial yet often misunderstood. This qualitative study explores the complex dynamics of workforce commitment by investigating 30 respondents across organizational levels through interviews, observations, and document analysis. The research identifies five key dimensions of loyalty: compensation, organizational climate, career development, transformational leadership, and team cohesion. Findings reveal that loyalty extends beyond traditional economic contracts, emerging as a sophisticated social construct shaped by intricate workplace interactions. Unlike conventional approaches that view loyalty through a transactional lens, this study provides a holistic perspective emphasizing psychological, social, and professional factors. The research demonstrates that employee commitment results from multifaceted organizational experiences rather than simple monetary exchanges. Managerial implications highlight the need for comprehensive strategies that address diverse aspects of employee experience, creating a supportive ecosystem that nurtures long-term organizational engagement and workforce stability.